Framework of Computer Science Learning Through Hybrid Service Learning Oriented Visual Toward the Continuum of Visualization Thinking and Generic Skills - Majid, Umi Mastura Abd; Atan, Noor Azean; Rukli, Rukli; Khan, Aqeel (Indian Journal of Information Sources and Services, 2024)
Computer Science learning requires students to think logically and understand its practical implementation in real-life situation clearly. However, the lack of learning activities that bridge the gap between theory and practice hinders their ability to depict learned concepts in real-world scenarios and master generic skills. Therefore, Computer Science education necessitates visualising learning concepts in real-life contexts, such as implementing Service Learning activities. However, in the current post-COVID-19 endemic situation, it is not feasible to implement this approach fully face-to-face. Thus, integrating Service Learning activities through technology-mediated means is essential in Computer Science education. Hybrid Service Learning activities, using technology as a medium, are instructional designs that provide opportunities for students to apply theoretical knowledge practically in real-life situations. Therefore, in this study, Computer Science learning activities were designed with visual materials through a hybrid service learning website to support the continuum of students’ visual thinking and their generic skills. Subsequently, the effects of Computer Science learning activities on the continuum of students’ visual thinking, level of generic skills, and perception were analyzed. A quasi-experimental study design was used, which involved a total of 27 respondents and took 15 weeks to complete. The research data was analyzed using descriptive analysis and inferential statistics. The results of paired t-test for the continuum of students’ visual thinking levels, including visual thinking, visual learning, and visual communication, indicated an improvement with a significant difference of [p<0.05] between the pre- and post-activities. In terms of students’ generic skills levels, the paired t-test for the pre-Service Learning [PS], during-Service Learning [DS], and post-Service Learning [AS] phases showed a significant difference of [p<0.05], which indicated an increase in students’ mastery of skills and changes between each phase. Furthermore, students’ perceptions revealed positive feedback towards hybrid service learning. Overall, based on the findings of this study, a framework for visual-based hybrid service learning was developed as a guide for Computer Science education to support the continuum of students’ visual thinking and their level of generic skills.